Cohort study showing correlation of Vitamin D levels with severity of illness in children admitted with acute febrile illness - Badjate, Priyanka; Prasad, Brijendra (Indian Journal of Child Health, 2020)
Background: Acute febrile illness (AFI) which is characterized by illness without any identified source has been less explored. However, no studies have correlated AFI, its various etiologies along with stay in hospital duration, and admission in paediatric intensive care unit (PICU) with Vitamin D levels as per our knowledge. Objective: The present study was conducted with a cohort of children having Vitamin D deficiency (VDD) and individuals with adequate levels of Vitamin D and a correlation among them was tried to be established. Materials and Methods: We conducted this study at the pediatric department of a tertiary hospital of Western India using the standard protocol. We determined severity of illness using six observational items and their scales as per acute illness observation scale (AIOS). Laboratory investigations such as complete hemogram, renal function tests, liver function tests, bacteriology cultures, radiography, and sonography were done as per indication. Serum calcium, serum phosphorous, and serum alkaline phosphatase levels were evaluated in all patients. Evaluation of Vitamin D status was done in all children within 48 h of admission to the hospital using chemiluminescent immunoassay method. Outcome parameters such as the duration of hospital stay and final outcome as discharged or death were noted. Results: We found bronchiolitis as the major etiology in most of the AFI cases. The children which required NICU admission had VDD. Children, who had AIOS score >10, indicating that severity of disease was also maximum from VDD group. Moreover, the hospital stay of VDD group was significantly higher. Conclusion: Overall data suggested that condition of children with AFI deteriorated more in the group which are deficient in Vitamin D suggesting that supplementation of Vitamin D could be fruitful strategy to reduce the disease severity.